Assay of Some Hydrolytic and Oxidative Enzymes Produced Extracellularly and Intracellularly by Colletotrichum gloeosporioides Penz. Causing Anthracnose Disease in Mango - Kabir, Md Golam; Islam, Md Rafiqul; Sikdar, Dwaipayan; Absar, Nurul (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Anthracnose; Colletotrichum gloeosporioides Penz; Extracellular enzyme; Intracellular enzyme; Enzyme activity Bangladesh j. genet. biotechnol. 7(1&2): 53-56 2006 (June & December)